Evaluation of antioxidant and antibacterial activities of the stems of Flammulina velutipes and Hypsizygus tessellatus (white and brown var.) extracted with different solvents - Rashid, Shah Samiur; Ukaegbu, Chinonso Ishmael; Hazrulrizawati, Hamid; Alara, Oluwaseun Ruth (Springer International Publishing, 2018)
Mushrooms are rich in pharmacologically-important phytochemicals with reported medicinal values. In this study, the antibacterial activity of Flammulina velutipes (Enoki), Hypsizygus tessellatus (brown (Buna shimeji) and white (Bunapi shimeji) variants) stem extracts prepared with different solvents (water, methanol, acetone, and ethyl acetate) was investigated against Escherichia coli (E. coli ATCC 25922), Serratia marscenscens (S. marscenscens ATCC14756), Bacillus subtilis (B. subtilis ATCC 23857), and Staphylococcus aureus (S. aureus ATCC 25923). Their antioxidant activities were evaluated using radical scavenging assays of 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydrogen peroxide (H2O2) and ferric reducing power (FRP). The water extracts of Enoki, Buna shimeji, and Bunapi shimeji showed bacterial growth inhibition in a concentration-dependent manner. From the obtained results, all the Enoki extracts showed a significant inhibition of the gram positive bacterial species (E. coli and S. marcescens > 68%) and a reduced inhibition of the gram negative bacterial species (B. subtilis and S. aureus < 45%, p < 0.05) after 24 h of incubation, while water extracts of Buna shimeji showed a significantly lower bacterial growth inhibition (< 60%) against all the studied bacteria. Bunapi shimeji extract inhibited S. marscenscens, E. coli, B. subtilis, and S. aureus by 54, 67, 46, and 44%, respectively. Methanol, acetone and ethyl acetate extracts showed significantly lower antibacterial activities (p < 0.05) compared to water extracts. Similarly, water extracts of Enoki, Bunapi shimeji and Buna shimeji showed significant antioxidant activities using DPPH (67.37 ± 0.01, 66.30 ± 0.18 and 42.44 ± 0.18%, respectively), hydrogen peroxide (67.87 ± 0.000, 45.52 ± 0.160 and 52.08 ± 0.000% respectively), and FRP (0.891 ± 0.001, 0.413 ± 0.001 and 0.491 ± 0.001, respectively) at the concentration of 1 mg/mL, compared to their respective methanol, acetone and ethyl acetate fractions. Upon LC-MS analysis of the most potent fraction (Enoki water extract), several phenolic compounds were identified, of which chromogenic acid, Methyl-5-O-caffeoylquinate, Kukoamine A, Kushenol K, Methyl Kushenol C, Glabrol, Sanggenon J, Corylin, and Moracenin C were confirmed. The antioxidant activities of the water extracts of Enoki, Buna shimeji and Bunapi shimeji correlated with their total phenolic and flavonoid contents, which were (166.56 ± 1.50, 108.13 ± 0.32 and 116.71 ± 0.01 µg gallic acid equivalent (GAE)/mg, respectively) and (96.33 ± 0.03, 82.18 ± 0.20 and 91.37 ± 0.15 µg quercetin equivalent (QE)/mg, respectively). Collectively, the study results have shown the studied mushrooms as potential natural sources of pharmacological agents